Josh - Shigeru Chiba; Kiyoshi Nakagawa (Proceedings of the 3rd international conference on Aspect-oriented software development, 2004)
BACKGROUND: We examined trends in physical activity (PA), sedentary behavior (SB), and weight status among Korean adolescents across the COVID-19 period and assessed subgroup disparities. METHODS: We analyzed nationally representative data from the 2017 to 2024 Korea youth risk behavior web-based survey (N = 417,243; mean age, 15.0 years). PA adherence followed World Health Organization recommendations; SB adherence was defined as ≤ 2 h/day of recreational screen time; and weight status used the 2017 Korean Growth Chart BMI percentiles. Weighted estimates and Joinpoint regression quantified annual percent changes (APCs). RESULTS: Underweight and obesity both increased. Underweight rose particularly among girls (APC, 6.7%), whereas obesity was more prevalent among boys (14.7%; APC, 3.2%) and high school students (13.3%; APC, 3.2%). PA adherence increased over the study period (APC, 4.0%) but remained low, especially in girls (2.4% vs. 8.6% in boys). SB adherence declined from 36.1% in 2017 to 19.2% in 2020 and partially recovered by 2024 (24.5%). IMPLICATIONS FOR SCHOOL HEALTH POLICY, PRACTICE, AND EQUITY: Schools should adopt gender-sensitive strategies to increase daily PA and reduce recreational SB, prioritizing girls and high school students. CONCLUSIONS: From 2017 to 2024, weight polarization worsened among Korean adolescents, underscoring the need for equitable school-based interventions targeting PA, SB, and weight-related disparities.